Autism Dan Intervensi Penanganannya Pada Salah Satu Siswa di Pendidikan Anak Usia Dini - Nuri Arifiah Romadhoni; Pamuji (Student Research Journal, 2024)
This research aims to introduce the characteristics of children with autism and interventions to treat them. This refers to the child's daily behavior both at school and at home. And also several therapies that have been carried out, the impact of several interventions that have been carried out. carried out produces several benefits that are useful for stimulating children's development in the cognitive and social fields, even though it is gradual and slow. Autism is a neurodevelopmental disorder that affects communication, social interactions, and behavior. Every child with autism is unique, but there are several common behaviors and treatment methods that are often used. This research is about children who have autism, children have very visible behavioral deviations, so they need special intervention to handle them. Handling children with autism involves an individual approach and often requires a combination of various methods. The impacts of the behavior they carry out at school require intervention by going to psychiatrists and other treatments that help their psychological development.